Wax Deposits on Leaf-Surfaces of Two Clones of Panicum repens Grown in Contrasting Environments - Soedharoedjian Ronoprawiro (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 1979)
-